Revisiting elevated HDL cholesterol, cerebral hemodynamic improvement in asymptomatic carotid artery disease: A longitudinal 15O-Gas PET study - Hattori, Yorito; Abe, Soichro; Kakino, Yoshinori; Nakaoku, Yuriko; Ogata, Soshiro; Nishimura, Kunihiro; Iida, Hidehiro; Ihara, Masafumi (Springer Nature, 2026)
Interventional trials with high-density lipoprotein cholesterol (HDL-C)-raising drugs have generally failed to demonstrate a beneficial effect on cardiovascular outcomes, although low HDL-C levels confer the risk of cerebrocardiovascular diseases. Previous experimental studies indicate that HDL-C promotes angiogenesis/arteriogenesis. Therefore, we aimed to clinically investigate whether high blood HDL-C levels could clinically predict cerebral hemodynamic improvements in patients with asymptomatic carotid artery stenosis/occlusion showing cerebral hypoperfusion. This longitudinal retrospective observational study included a total of 66 hemispheres governed by asymptomatic carotid artery stenosis/occlusion in patients who underwent 2-time multi-parametric 15O-gas positron emission tomography (PET). The longitudinal changes of multiple parameters, including cerebral blood flow (CBF), cerebral blood volume (CBV), cerebral metabolic rate of oxygen, and oxygen extraction fraction (OEF) values were scrutinized between patients with high and low baseline blood HDL-C levels. The cerebral hemodynamic parameters were normalized to the bilateral cerebellum. The median interval between PET examinations was 212.0 and 219.0 days for patients with low and high HDL-C levels, respectively (p = 0.91). A high blood HDL-C level was an independent predictor of increasing CBF (β [mean difference]: 0.035, 95 % confidence interval [CI]: 0.010–0.060), and CBV (β: 0.26, 95 % CI: 0.023–0.50), and decreasing OEF (β: −0.041, 95 % CI: −0.077 to −0.006) in the anterior circulation territory. A high blood HDL-C level was clinically an independent predictor of cerebral hemodynamic improvement. HDL-C could be an important therapeutic target for ischemic stroke prevention by improving cerebral hemodynamic parameters presumably via angiogenesis and arteriogenesis especially in patients showing cerebral hypoperfusion.